2021
DOI: 10.7554/elife.63880
|View full text |Cite
|
Sign up to set email alerts
|

Micron-scale geometrical features of microtubules as regulators of microtubule organization

Abstract: The organization of micron-sized, multi-microtubule arrays from individual microtubules is essential for diverse cellular functions. The microtubule polymer is largely viewed as a passive building block during the organization process. An exception is the ‘tubulin code’ where alterations to tubulin at the amino acid level can influence the activity of microtubule-associated proteins. Recent studies reveal that micron-scale geometrical features of individual microtubules and polymer networks, such as microtubul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 188 publications
(226 reference statements)
0
6
0
Order By: Relevance
“…Microtubule polymers, composed of linear protofilaments of α, β‐tubulin heterodimers, form the backbone of diverse cellular structures such as the spindle in dividing cells and axonemes in cilia. In these structures, individual microtubules are arranged in arrays of well‐defined size and geometry (Mani et al., 2021). For instance, anti‐parallel microtubule arrays form the midzone of the mitotic spindle, and parallel arrays of microtubule doublets comprise the axoneme.…”
Section: Introductionmentioning
confidence: 99%
“…Microtubule polymers, composed of linear protofilaments of α, β‐tubulin heterodimers, form the backbone of diverse cellular structures such as the spindle in dividing cells and axonemes in cilia. In these structures, individual microtubules are arranged in arrays of well‐defined size and geometry (Mani et al., 2021). For instance, anti‐parallel microtubule arrays form the midzone of the mitotic spindle, and parallel arrays of microtubule doublets comprise the axoneme.…”
Section: Introductionmentioning
confidence: 99%
“…The constitutive relationship between local stress and microtubules dynamics was devised from recent experiments showing that a tensile force up to ~10 pN increases the polymerization rate and the rescue frequency but decreases the depolymerization rate and the catastrophe frequency (39). The range of stress on the cell wall that we estimated from the previous FE model is [3][4][5][6][7][8][9][10][11][12][13][14][15]. If microtubules feel this large stress directly, the magnitude of forces from the stress is far beyond level that microtubules can sustain without rupturing (46).…”
Section: Constitutive Relationship Between Local Stress and Microtubu...mentioning
confidence: 99%
“…The collision-induced catastrophe and zippering are known to mediate ordered cortical microtubule arrays emerging at cellular scales. It was shown that a balance between steep-angle catastrophe and shallow-angle zippering are necessary and sufficient for promoting self-organization and parallel configuration of microtubules (9, 15). Regardless of collision, microtubules undergoing rapid shrinkage can transition to a growth state, which is called rescue.…”
Section: Introductionmentioning
confidence: 99%
“…The response of the MT lattice to a crushing force (possibly induced by a severing enzyme) and healing from the breakage have been understood using coarse-grained molecular dynamics simulation [55]. A recent review [56] has proposed two mechanisms to understand severing-induced MT amplification. Firstly, there can be competition between tubulin addition and tubulin dissociation by severing enzymes.…”
Section: Introductionmentioning
confidence: 99%